THE PHARMACOKINETICS OF APIXABAN IN PATIENTS WITH CARDIOEMBOLIC STROKE IN ACUTE PHASE - A. V. Kryukov; D. A. Sychev; D. A. Andreev; A. V. Ryabova; N. P. Denisenko; M. A. Loskutnikov; O. I. Vinogradov; M. A. Domashenko (Столичная издательская компания, 2016)
Aim. To study pharmacokinetics of apixaban in patients with atrial fibrillation and cardioembolic stroke in acute phase. Material and methods. 17 patients (14 women and 3 men), aged 76.6±9.5 years with atrial fibrillation and cardioembolic stroke in acute phase were enrolled into the study. High performance liquid chromatography mass spectrometry analysis was used to determine apixaban plasma concentration. Results. Intake of a single dose of apixaban 5 mg is described by the following pharmacokinetic parameters: geometric mean of Cmax 124.5 ng/mL (CV%=48), AUC (0, τ) 1008.0 ng•h/mL (CV%=48), AUC (0, ∞) 2751.6 ng•h/mL (CV%=82), median Tmax 3 hours (min 1, max 4), mean t½ 16.9 h (SD 13.6). Negative correlation between NIHSS stroke severity score and Tmax was found (r=-0.628, p=0.007) as well as positive correlation between apixaban t½ and patient age (r=0.638, p=0.01). A tendency to increase in AUC (0, ∞) was observed according to CHA2DS2-VASc points amount but it did not reach the statistical significance (r=0.620, p=0.14). Conclusion. For the first time in Russia pharmacokinetic data of apixaban were obtained in patients with cardioembolic stroke in acute phase. It could be the basis for the development of new personalized approaches to anticoagulation therapy in these patients. Keywords: new oral anticoagulants, apixaban, pharmacokinetics, atrial fibrillation, cardioembolic stroke